Financing the Transition of Previously Centrally Planned Economies : Macroeconomic Effectson Western Europe - Symansky, Steven (IMF Working Papers; Working Paper ;, 1994)
Under alternative assumptions on the likely developments in external financing of PCPE transition, and based on a multi-country, forward-looking model that includes a simplified PCPE block, we simulate the response of PCPEs to a transfer of capital from the industrial countries, and assess the potential implications for Western Europe over the next ten years. Real interest rates in Western Europe are likely to experience only mild upward pressure, and most macroeconomic aggregates are likely to change by substantially smaller magnitudes than typical over the business cycle.